Rancangan Kurikulum Pendidikan Anak Usia Dini (PAUD) Di Sekolah Binaan Pemerintah Kota Bekasi - Fathana Gina; Sandra Adetya Syarif; Nurwahyuni Nasir; Timorora Sandha Perdhana (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2020)
Abstract PAUD has the main function of developing all aspects of a child's development, including cognitive development, language, physical (gross and subtle motoric), social, emotional. Planning a curriculum for children, teachers must have a goal, how to organize curriculum content, choose the form of learning experience for children, how the sequence of lessons is given and then determine how to do an assessment of children's learning outcomes and the program itself. Planning a curriculum for children, teachers must have a goal, how to organize curriculum content, choose the form of learning experience for children, how the sequence of lessons is given and then determine how to do an assessment of children's learning outcomes and the program itself. At present there are still PAUD that do not yet have a structured learning curriculum such as what happened in PAUD assisted by the Bekasi City Government. This then impacts on learning activities that are less directed. Children who attend PAUD at the school are more often left to play without direction from their teacher. Therefore, this community service activity is considered necessary to help teachers in PAUD assisted by the Bekasi City Government to have a curriculum that can be a guide so that the teaching and learning process becomes more structured and directed. The output of this community service activity is in the form of a PAUD curriculum design that can be used as a learning reference for students participating in the PAUD Guidance at the Bekasi City Government. The result is that teachers get new insights about teaching programs and can develop learning strategies for students. Keywords: PAUD, Curriculum, Syllabus Abstrak PAUD memiliki fungsi utama mengembangkan semua aspek perkembangan anak, meliputi perkembangan kognitif, bahasa, fisik (motorik kasar dan halus), sosial, emosional. Merencanakan suatu kurikulum untuk anak, guru harus memiliki tujuan, bagaimana mengorganisasi isi kurikulum, memilih bentuk pengalaman belajar bagi anak, bagaimana urutan pelajaran diberikan dan kemudian menentukan bagaimana melakukan penilaian terhadap hasil belajar anak dan program itu sendiri. Merencanakan suatu kurikulum untuk anak, guru harus memiliki tujuan, bagaimana mengorganisasi isi kurikulum, memilih bentuk pengalaman belajar bagi anak, bagaimana urutan pelajaran diberikan dan kemudian menentukan bagaimana melakukan penilaian terhadap hasil belajar anak dan program itu sendiri. Saat ini masih ada PAUD yang belum memiliki kurikulum pembelajaran yang terstruktur seperti yang terjadi di PAUD binaan Pemerintah Kota Bekasi. Hal ini kemudian berdampak pada kegiatan pembelajaran yang kurang terarah. Anak yang mengikuti PAUD di sekolah tersebut lebih sering dibiarkan bermain tanpa arahan dari gurunya. Oleh karena itu, kegiatan pengabdian masyarakat ini dianggap perlu untuk membantu guru di PAUD binaan Pemkot Bekasi agar memiliki kurikulum yang dapat menjadi pedoman sehinga proses pengajaran dan pembelajaran menjadi lebih terstruktur dan terarah. Luaran kegiatan pengabdian masyarakat ini berupa rancangan kurikulum PAUD yang dapat dijadikan acuan pembelajaran bagi siswa-siswa yang mengikuti PAUD Binaan Pemkot Bekasi. Hasilnya guru mendapatkan wawasan baru mengenai proram pengajaran dan dapat mengembangkan strategi pembelajaran pada siswa. Kata kunci: PAUD, Kurikulum, Silabus